MORPHOGENESIS OF BRANCHIOGENIC GLANDS OF THE NECK IN THE FETAL PERIOD OF ONTOGENESIS - О. Білоокий; Т. Хмара; Д. Проняєв; В. Безрук (Неонатологія, хірургія та перинатальна медицина)
Branchiogenic glands play an important role in the control of calcium and iodine levels and thus have a direct impact on muscle contraction and neurotransmission. Variations in the structure and ectopic location of parathyroid and thyroid glands increase the complexity of thyroid and parathyroid surgery.